2021
DOI: 10.4103/ccd.ccd_760_20
|View full text |Cite
|
Sign up to set email alerts
|

Stereomicroscopic Evaluation of Microcrack Formation in Dentin by ProTaper Next, Revo S, and WaveOne Gold File System

Abstract: Background: During the biomechanical preparation of the root canal by rotary file systems, stress is generated within the canal, which leads to dentinal microcrack formation. Such defects are evaluated only under the microscope. Aim: The present study aimed to evaluate dentinal microcrack formation after instrumentation with ProTaper Next (M-wire), Revo S (conventional NiTi), and WaveOne Gold (Gold-wire) file systems under the stereomicroscope. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…There was a high level of newly formed microcracks in group MWOG, especially in the middle third (20.41%). This result contrasts a previous study, which found less crack formation occurred with WOG ( 20 ). This discrepancy may be due to the previously mentioned study being conducted on single-rooted teeth ( 20 ); hence, there would have been less contact between the instrument and root surface, resulting in minimal stress and less crack formation.…”
Section: Discussioncontrasting
confidence: 99%
“…There was a high level of newly formed microcracks in group MWOG, especially in the middle third (20.41%). This result contrasts a previous study, which found less crack formation occurred with WOG ( 20 ). This discrepancy may be due to the previously mentioned study being conducted on single-rooted teeth ( 20 ); hence, there would have been less contact between the instrument and root surface, resulting in minimal stress and less crack formation.…”
Section: Discussioncontrasting
confidence: 99%
“…De-Deus et al 33 reported that the microcracks in the root dentin were caused by the extracted teeth, so the results of the studies reporting the presence of microcracks were flawed. Although it is not possible to exclude the possibility that these factors may also cause microcracks in root dentin (34), it is a strong evidence that no cracks were observed in the non-instrumented but sectioned control groups in several stereomicroscope studies (5)(6)(7)11,19,22,(35)(36)(37). Hereby, the aforementioned factors are unlikely to affect the findings (34).…”
Section: Discussionmentioning
confidence: 97%
“…The differences in the results of the studies included in this revision are, therefore, attributable to many factors and are not related to the taper of the instrumentation used, but instead are probably related to: The difference in the preparation motion [ 48 , 55 , 56 ]; The cross-sectional profile and blade design [ 10 , 63 , 64 ]; The type of alloy of the instrument used [ 54 , 64 , 65 , 66 ]. …”
Section: Discussionmentioning
confidence: 99%